Scanning Electron Microscopic Evaluation of the Sealer-Dentine Interface of Three Sealers - Mohammadian, Fatemeh; Farahanimastry, Farzad; Dibaji, Fatemeh; Kharazifard, Mohammad Javad (Iranian Endodontic Journal, 2017)
Introduction: This study aimed to evaluate the dentin-sealer interface in three different sealers using scanning electron microscopy (SEM). Methods and Materials: Thirty extracted human single-rooted teeth were prepared using ProTaper rotary files and were randomly divided into three groups (n=10) including BC Sealer, AH-Plus and Dorifill. The root canals were filled with cold lateral condensation technique and stored for 7 days in 100% humidity at 37°C. Cross sections were prepared from the coronal, middle, and apical sections of the roots. Then SEM images were taken and the width of gaps was measured by software. Sectional images were evaluated by two endodontists. Data were analyzed using two- and one-way ANOVA and Kruskal-Wallis tests. Results: The mean gap width was significantly lower in coronal area in BC Sealer group compared to Dorifill (P=0.043) and likewise in AH-Plus group compared to Dorifill (P=0.018). There was no significant difference between BC Sealer and AH-Plus group in this area (P=0.923). No significant difference was detected in apical and middle zones among three sealers (P=0.367 and 0.643, respectively). Dentin-sealer interface showed no significant difference in three sealers in the apical area (P=0.051), but dentin-BC Sealer interface was better than AH-Plus in middle and coronal areas, and both outperformed Dorifill (P=0.001). Conclusion: BC Sealer and AH-Plus had less gaps than Dorifill in coronal area. In addition, BC Sealer had better dentin interface in middle and coronal area compared to AH-Plus, and both performed better than Dorifill. Reverse relationship was observed between the mean gap width and dentin-sealer interface quality. Keywords: Endodontic Sealer; Interface; Gap; Root Sealer; Scanning Electron Microscopy